2015
DOI: 10.11149/jkaoh.2015.39.3.168
|View full text |Cite
|
Sign up to set email alerts
|

Growth inhibition effect ofRubus coreanusMiquel onCandida albicans

Abstract: This is an open-access article distributed under the terms of the Creative Commons Attribution Non-Commercial License (http://creativecommons.org/licenses/by-nc/4.0/), which permits unrestricted non-commercial use, distribution, and reproduction in any medium, provided the original work is properly cited.Objectives: In this study, the growth inhibition effect of Rubus coreanus Miquel on Candida albicans (C. albicans) was observed. Methods: The Rubus coreanus Miquel was extracted with 70% methanol and concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…The statistical analysis was performed with IBM SPSS ver. 21.0 (IBM Co., Armonk, NY, USA). The antibacterial effect were analysed through one-way ANOVA and Tukey's post hoc test at a 0.05 significance level.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The statistical analysis was performed with IBM SPSS ver. 21.0 (IBM Co., Armonk, NY, USA). The antibacterial effect were analysed through one-way ANOVA and Tukey's post hoc test at a 0.05 significance level.…”
Section: Discussionmentioning
confidence: 99%
“…Seong et al [20] reported that gallnut extract using methanol showed antifungal activity against C. albicans. Shin et al [21] investigated the antifungal activity of raspberry extract at various concentrations (2,4,8,15,30,60, and 120 mg/ml) against C. albicans and reported that bacterial growth inhibition was shown from the 8 mg/ml concentration of the extract. Choi et al [22] applied Acanthopanax sessiliflorum extract against C. albicans, and the results showed an antibacterial effect at 20 mg/ml while no bacteria were observed at 50 mg/ml.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A. actinomycetemcomitans causes aggressive periodontal disease and colonizes dental plaque 19,20) . C. albicans is a normal flora in the non-pathogenic state, but attaches to oral epithelial cells or dentures of patients with weakened immune systems and causes opportunistic infections and candidiasis 21) . The main components of AGN are coumarin, a lipid-soluble substance, and polysaccharide, a water-soluble substance 22) .…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…sobrinus, which were cultured adding plum blossom extracts, using a scanning electron microscope and reported that there was damage to the surface of some bacteria. Shin et al 17) also observed C. albicans, which was cultured adding R. coreanus extracts, using a scanning electron microscope and reported that there was damage to some cells.…”
Section: )mentioning
confidence: 99%